Interaction of cisplatin with a CCHC zinc finger motif‡. (19th February 2013) - Castiglione Morelli, Maria Antonietta; Ostuni, Angela; Cristinziano, Pier Luigi; Tesauro, Diego; Bavoso, Alfonso
Abstract : The interaction between cisplatin and an 18‐residue CCHC zinc finger motif derived from a retroviral nucleocapsid protein (PyrZf18) has been studied using UV–visible, CD and 1 H NMR spectroscopies and ESI‐MS spectrometry. Cisplatin irreversibly blocks the cysteine zinc binding groups in the free peptide and is able to slowly eject zinc from the zinc–peptide complex. The observed end product of the reaction with cisplatin is a complex in which only one ammonia molecule is coordinated to platinum. After an initial binding with two cysteine residues and the formation of the (PyrZf18)–platinum–(NH3 )2 complex, a release of one ammonia molecule occurs because of trans ‐labilization, and the third cysteine is coordinated, leading to a mixture of isomers and/or conformers of the (PyrZf18)–platinum–NH3 complex. The results are discussed with respect to the potential antiretroviral activity of platinum(II) compounds and to the possible interaction of cisplatin with the cellular nucleic acid binding proteins. Copyright © 2013 European Peptide Society and John Wiley & Sons, Ltd. Abstract : This study is focused on the interaction between cisplatin and an 18‐residue CCHC zinc finger motif derived from a retroviral nucleocapsid protein (PyrZf18) UV–visible, CD and 1 H NMR spectroscopies and ESI‐MS spectrometry. The results are discussed with respect to the potential antiretroviral activity of platinum(II) compounds and to the possible interaction of cisplatin with the cellular nucleic acid binding proteins.